Cracking the code of neuronal apoptosis and survival - Cavallaro, S (Cell Death Dis, 2015)
Neuronal apoptosis and survival are tightly controlled processes that regulate cell fate during the development of the central nervous system and its homeostasis throughout adulthood. A new study in primary cultures of cerebellar granule neurons identified common transcriptional cascades during rescue from apoptosis by insulin-like growth factor-1 (Igf1) and pituitary adenylyl cyclase-activating polypeptide (Pacap), thus suggesting the existence of a high degree of conservation of cell survival pathways.